Molecular dynamics study on the elucidation of polyamide membrane fouling by nonionic surfactants and disaccharides. Issue 36 (6th September 2021) - Kawabata, Yuki; Gonzales, Ralph Rolly; Nakagawa, Keizo; Shintani, Takuji; Matsuyama, Hideto; Fujimura, Yu; Kawakatsu, Takahiro; Yoshioka, Tomohisa
Abstract : Reverse osmosis (RO) is a widely used energy-efficient separation technology for water treatment. Abstract : Reverse osmosis (RO) is a widely used energy-efficient separation technology for water treatment. Polyamide (PA) membranes are the conventional choice for this process. Fouling is a serious problem for RO separation. This issue leads to significant decreases in the water permeability of PA membranes, and it has yet to be fully elucidated. In particular, the fouling behavior of a nonionic substance on the negatively charged surface of a PA membrane in an aqueous environment has not been previously studied. In this work, the mechanisms of nonionic substances such as polyoxyethylene octyl ether (PE5) and maltose (Mal) were investigated using molecular dynamics (MD) simulations. In a PA membrane in which the carboxyl group was not dissociated, the hydrophobic portion of the membrane was exposed due to the localization of water molecules around the carboxyl groups in the PA membrane. This caused hydrophobic interaction with the hydrophobic groups of PE5. In the case of an amine-modified PA membrane containing no carboxyl groups, water was not localized around the functional group, and the water orientation of the polyamide surface was also low. Due to this membrane property, the presence of stabilized water around PE5 reduced the number of hydrophobic interactions. In similar manner, a PA membrane with a slightly dissociated carboxyl group was hydrophilic, which reduced the PE5 adsorption. The presence of many dissociated carboxyl groups, however, enhanced the adsorption of PE5 due to the increase in interactions between the dissociated carboxyl groups and the hydrophilic groups of PE5. Therefore, PE5 exhibited an amphipathic adsorption wherein both hydrophilic and hydrophobic groups contributed to adsorption onto the PA membrane. Mal, on the other hand, was highly stable in every aqueous environment independent of the state of the functional groups of the PA membrane, and was not easily affected by the properties of the PA membrane.